Inflammatory phenotype of osteoarthritis and its potential therapies. Issue 2 (20th December 2021) - Cao, Yumei; Tang, Su'an; Ding, Changhai
Abstract: Introduction: Osteoarthritis (OA) is the most common joint disorder in the world but there are no approved therapies to slow disease progression. Historically, OA has been considered a wear and tear joint disease and efforts to identify and develop disease modifying therapies have primarily focused on inhibiting cartilage degradation directly. However, increasing studies have suggested that inflammation is a key player of joint pathology in some OA patients and also a link between obesity and OA. Therefore, targeting inflammation in these patients could be a promising therapeutic strategy. Areas Covered: In this review, we collate the latest evidence on the relationship between inflammation and OA which allows to propose the inflammatory phenotype of OA, and summarize major results of some emerging therapies targeting this phenotype in clinical trials which could implicate future directions for OA treatment. Expert Opinion: The authors believe early diagnosis, phenotyping OA patients and precise therapies would expedite the development of DMOADs targeting OA inflammatory phenotype. In the future, well‐designed clinical trials including appropriate subgroups or phenotypes of patients according to underlying causes and mechanisms of OA are expected for investigational therapies. Highlights: This review summarize the major results of some emerging therapies targeting inflammatory phenotype in clinical trials, implying future directions for OA treatment. This work provide a new perspective to develop true DMOADs that target the OA inflammatory phenotype. Abstract : OA phenotypes and emerging therapies for the inflammatory phenotype.